Goodwill of Companies: the Need to Build and Problems - E. Yu. Kuzmina; I. V. Soklakova (Управление)
In article the importance of business reputation as necessary factor of increase in competitiveness of the companies is proved, stages of formation of business reputation of the company are considered, the reputation is considered as one of the most important components of intangible assets of the company, examples of increase in business reputation of the modern organizations are described, the main advantages which the positive business reputation of the company gives are distinguished, described external and internal factors and risks, the exerting considerable impact on reputation of the company.